2013
DOI: 10.2337/db12-0495
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum Metabolites Associated With Risk of Type 2 Diabetes Using a Targeted Metabolomic Approach

Abstract: Metabolomic discovery of biomarkers of type 2 diabetes (T2D) risk may reveal etiological pathways and help to identify individuals at risk for disease. We prospectively investigated the association between serum metabolites measured by targeted metabolomics and risk of T2D in the European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam (27,548 adults) among all incident cases of T2D (n = 800, mean follow-up 7 years) and a randomly drawn subcohort (n = 2,282). Flow injection analysis tandem m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

105
759
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 871 publications
(892 citation statements)
references
References 56 publications
105
759
7
3
Order By: Relevance
“…Several of these metabolites include classes of lipids (i.e. lysophosphatidylcholines, phosphocholines and sphingomyelins), which have been shown to be associated with insulin secretion 36. This provides further evidence of kisspeptin's modulation of human metabolism, which (with further study) may provide important mechanistic data.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Several of these metabolites include classes of lipids (i.e. lysophosphatidylcholines, phosphocholines and sphingomyelins), which have been shown to be associated with insulin secretion 36. This provides further evidence of kisspeptin's modulation of human metabolism, which (with further study) may provide important mechanistic data.…”
Section: Discussionmentioning
confidence: 72%
“…Linear mixed effect modelling27 was used to identify patterns of serum metabolites, which changed significantly between baseline (T = −15 minutes) and steady state (T = 45 minutes) during kisspeptin but not vehicle administration. The profiles of numerous small molecules (Figure S4) and lipid species (Figure 3) were altered, including lysophosphatidylcholine (LPC 18:2), which was reduced by kisspeptin administration and has previously been shown to be negatively correlated with insulin secretion 36. All annotated metabolites that significantly changed during kisspeptin administration (but not vehicle administration) have been collated in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the Biocrates AbsoluteIDQ p150 kit allows for the quantification of hexose, which is ß90-95% glucose (Goek et al, 2012) and this is an important source of energy for the body. Indeed, metabolites as detected using this sample preprocessing kit have been associated previously with various diseases and other conditions (see, e.g., Floegel et al, 2013;He et al, 2012;Jourdan et al, 2012;Mittelstrass et al, 2011;Wang-Sattler et al, 2012;Xu et al, 2013;.…”
mentioning
confidence: 99%
“…Furthermore, it was recently reported that pregnant women with high fasting plasma glucose concentrations also had high fasting concentrations of several amino acids, including leucine [37]. Higher fasting concentrations of BCAAs were also found in individuals with type 2 diabetes and insulin resistance [34,[38][39][40]. These findings indicate that alterations in BCAA metabolism are associated with gestational diabetes, insulin resistance and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, population-based studies of previously healthy adults revealed that low lyso-PC C18:2 concentrations were associated with an increased risk of pre-type 2 diabetes and type 2 diabetes [30,34], while high concentrations of several diacyl-PCs (C32:1, C36:1, C38:3 and C40:5) were associated with a risk of type 2 diabetes independent of dietary, lifestyle and anthropometric factors. In our study, the total lyso-PC/total PC ratio was significantly increased in women who had lactated for >3 months as a consequence of higher concentrations of several lyso-PCs and lower concentrations of several diacyl-PCs in these women.…”
Section: Discussionmentioning
confidence: 99%